ID: 195. Issue 1 (November 2015) - Avau, Anneleen; Imbrechts, Maya; Put, Karen; Brisse, Ellen; Mitera, Tania; Leclercq, Georges; Wouters, Carine H.; Matthys, Patrick
<x xml:space="preserve">Abstract</x> Objective: Systemic juvenile idiopathic arthritis (sJIA) is a rheumatic childhood disease, with distinctive systemic inflammatory features and a typical cytokine profile. The etiology of sJIA is largely unknown. Here, we aimed to elucidate the role of specific cell populations and cytokines in the pathogenesis, by means of a new mouse model of sJIA relying on the injection of complete Freund's adjuvant (CFA) in interferon-gamma deficient (IFN-g KO) mice. Wild type (WT) mice developed a minor inflammation, indicating that IFN-g provides protection in the disease process. Methods: Cytokine mRNA levels were analyzed in organs and purified immune cell populations of CFA-challenged IFN-g KO and WT mice. Cytokine antagonists and cell depleting antibodies were administered to mice. Clinical, laboratory and immune features of sJIA were evaluated. Results: In the diseased IFN-g KO mice, elevated expression of IL 1<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7n4h" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β</alternatives>, IL-6, IL-17 and IL-22 were found in lymph nodes and – remarkably – also in lung tissue. Gamma-delta T cells were a major cell source for IL-17, and anti-IL-17 antibodies abrogated the disease. In the non-diseased WT mice, expression of IFN-g was almost exclusively found in NK, NKT and gamma-delta T cells. Transient neutralization of IFN-g as well as depletion of NK cells in WT mice both resulted in a fulminant sJIA-like disease. Conclusion: These data pinpoint innate immune cells and non-lymphoid organs as important sources of cytokines in CFA-induced animal models. The results also demonstrate that NK cells provide a regulatory function in the pathogenesis of sJIA, by production of IFN-g.